Utilization Of Exhaust Air Conditioning In Apartments For Hot Water Supply: Overview Of Economic Aspects - Andreas, Andreas (Sean Institute, 2022)
The economic crisis that has hit almost all parts of the world has forced everyone to rethink their own economic arrangements. One thing to consider is the use of hot water. Not by eliminating it, but by looking for other alternatives to produce hot water. The heat-generating system that is widely used by the community is the electric water heater. On the one hand, this system works effectively because it can produce hot water with a maximum temperature of 750C. But on the other hand this system is not economical, because the electricity costs are very large. An alternative that can be given is the use of Air Conditioning Water Heater. Compared to the use of other types of water heaters, hot water produced by ACWH can be said to be